Unveiling Choice: Debate on the Use of Hijab Religious Studies and Feminism in Malaysia - Saphire, Anisya Olivia; Nurkhasanah, Dini Septianti; Istighfarin, Hanifah Pammula (Journal of ASEAN Dynamics and Beyond, 2021)
Hijab is an important symbol for Malaysia as a country that implements Islamic values in its social system. However, Maryam Lee sees that the decision of Malaysian Muslim women to wear the hijab is largely influenced by social demands. Maryam also sees that women who decide to take off their hijab are often criticized by society. These views Maryam wrote in her book entitled Unveiling Choices. In this book, Maryam narrates her views and decision to remove the hijab. Maryam also explained that women should be freed in deciding whether to wear or take off the hijab. This study aims to understand Maryam Lee's view of the hijab and how Malaysians respond to it. Therefore, this study will also look at the position of the hijab for the Malaysian people, Maryam Lee's thoughts on hijab, and the public's response to Maryam's thoughts. This research was conducted using a descriptive qualitative research method, namely by describing the thoughts of Maryam Lee and the public's response to her thoughts. Feminist Standpoint Theory chosen to understand Maryam's views and the public's response to her views. The results show that Maryam's view of the hijab contradicts the general view of Malaysian society. So that Maryam's view has sparked pros and cons from Malaysian society, this polarity occurs because there are groups who see Maryam's thoughts as a form of deviation from Islamic identity while other groups consider Maryam's actions as a form of resistance to the patriarchal system that demands justice for Malaysian women.